2018
DOI: 10.1371/journal.pone.0198299
|View full text |Cite
|
Sign up to set email alerts
|

Even subtle cultural differences affect face tuning

Abstract: Culture shapes social cognition in many ways. Yet cultural impact on face tuning remains largely unclear. Here typically developing females and males from the French-speaking part of Switzerland were presented with a set of Arcimboldo-like Face-n-Food images composed of food ingredients and in different degree resembling a face. The outcome had been compared with previous findings obtained in young adults of the South-West Germany. In that study, males exhibit higher thresholds for face tuning on the Face-n-Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…As in earlier studies with TD individuals and participants with neurodevelopmental disorders such as WS or ASD (Pavlova et al, 2015, 2016a,b, 2017b, 2018), children with DS either described a food-plate image in terms of food composition (non-face response, 0) or as a face (face response, 1). When an image had been seen as a face, DS individuals (similar to TD individuals) often exhibited emotional reaction such as smiling and astonishment.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…As in earlier studies with TD individuals and participants with neurodevelopmental disorders such as WS or ASD (Pavlova et al, 2015, 2016a,b, 2017b, 2018), children with DS either described a food-plate image in terms of food composition (non-face response, 0) or as a face (face response, 1). When an image had been seen as a face, DS individuals (similar to TD individuals) often exhibited emotional reaction such as smiling and astonishment.…”
Section: Resultsmentioning
confidence: 87%
“…By implementing the recently created Face-n-Food task consisting of a set of food-plate images that comprised food ingredients such as fruits, vegetables, and sausages (Pavlova et al, 2015, 2016a,b, 2017b, 2018), we examined face tuning in children with DS. The key benefit of Face-n-Food images is that their single components do not explicitly trigger face processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that adult women not only more readily report seeing a face (while men still see it as food composition), but also give more overall face responses, indicating the superiority of female brains in terms of face tuning. A later study reported that such gender specificity is subject to cultural modulation (Pavlova, Heiz, Sokolov, Fallgatter, & Barisnikov, 2018). Proverbio and Galli (2016) explored the neural underpinnings of the sex difference using event-related potential (ERP) technique.…”
Section: Sex Differences In Face Pareidolia Experiencementioning
confidence: 99%